Hubungan Pengetahuan Ibu Hamil Tentang Pencegahan Anemia Dalam Meningkatkan Kesehatan Ibu Hamil Di Wilayah Kecamatan Tabungenan - Jamilah, Sri; Sri Purwanti Ariani; Ernawati, Ernawati; Yuhansyah, Yuhansyah (Jurnal Sains Farmasi Dan Kesehatan, 2025)
Anemia in pregnant women is a significant health issue that can affect both the mother and the fetus, including the risk of preterm labor, low birth weight, and complications during delivery. Pregnant women's knowledge about anemia prevention plays a crucial role in improving their health during pregnancy. Factors such as poor dietary habits, low iron intake, and lack of awareness about the importance of antenatal care are the main contributors to the high prevalence of anemia. With adequate understanding of anemia prevention, pregnant women are more likely to maintain a nutritious diet, take iron supplements regularly, and undergo routine prenatal check-ups to ensure optimal health. In the Tabunganen District, knowledge levels among pregnant women regarding anemia prevention vary, influenced by factors such as education, access to information, and support from healthcare providers. Educational programs conducted by midwives and health workers play an essential role in raising awareness about balanced nutrition, iron supplementation, and the importance of regular check-ups at health facilities. By increasing knowledge and awareness of anemia prevention among pregnant women, the incidence of anemia is expected to decrease, thereby improving maternal and fetal health and reducing the risk of complications during pregnancy and childbirth